NARROW BAND ULTRAVIOLET B RADIATION THERAPY IN PATIENTS OF VITILIGO: UltravioletB Radiation Therapy - Rizvi, Syed Dilawar Abbas; Tabbasum, Saadia; Uddin, Rehan; Saleem, Khawar; Dar, Nasser Rashid; Rehman, Simeen Ber (Pakistan Armed Forces Medical Journal, 2008)
Objectives: To determine the efficacy of Narrow Band Ultra Violet B (NB-UVB) therapy to induce repigmentation in vitiligo patients with skin Fitzpatrick phototype IV.Study Design: Descriptive study.Place and Duration of Study: Department of Dermatology, PNS Shifa Karachi, from April 2004 to October 2005.Patients and Methods: Thirty-five patients were included in the study during a period of eighteen months starting from 23rd April 2004. Each patient had thrice weekly exposure to NB-UVB therapy on nonconsecutive days for a maximum period of one year. Results were evaluated clinically and by comparing digital photographs taken before, during and at the completion of treatment. Improvement was objectively assessed by grading it into four groups depending on percentage of re-pigmentation in the affected areas.  Results: Out of the 35 patients, two dropped out and 33 completed the course of therapy successfully.  The extent of vitiligo varied from 5% to 40% of body surface area. At the end of one year 9 (27.3%) patients had grade 4 recovery ( > 75% repigmentation), 15 (45.4%) had grade 3 recovery (50-75% repigmentation) and the rest had grade 2 recovery (25-50% repigmentation). No significant side effects were observed during the study period.Conclusions: Narrow-band UVB is a safe and effective treatment option for patients with Vitiligo.